The Effect of Wish and Drive with A Local Wisdom Approach on Knowledge and Motivation of Women for Cervical Cancer Screening - Pryati Rihi; Fransita Merkunita Agliyani Fiah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cervical cancer is a health problem with a morbidity and mortality rate that ranks among the 10 most common diseases among women. The high incidence of cervical cancer is caused by several factors, such as a lack of knowledge and motivation regarding cervical cancer prevention. This study applies the wish and drive method with a local wisdom approach, which is part of the behavioral change communication approach used in the context of health, especially in primary health care. The aims of this study is to prove the effectiveness of the wish and drive method with a local wisdom approach on the knowledge and motivation of WUS in cervical cancer screening. The research design is a quasi-experiment with a pretest and posttest two-group design. The sampling technique used was purposive sampling. Data analysis using univariate and bivariate analysis: Wilcoxon and Mann-Whitney tests. There were 90 women of childbearing age who were divided into an intervention group and a control group. A questionnaire was used to assess women's knowledge and motivation regarding cervical cancer screening is valid and reliable. Statistical analysis results showed that the wish and drive method with a local wisdom approach was effective in increasing the knowledge (p value=0.00) and motivation (p value=0.00) of women of childbearing age in preventing cervical. Based on the results of this study, it is recommended that the wish and drive method with a local wisdom approach be used as an alternative nursing intervention to address the problem of women's lack of knowledge and motivation in preventing cervical cancer.